2019
DOI: 10.1038/s41598-019-50982-8
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Hydrophobic Surfaces and Self-Cleaning Applications

Abstract: Hydrophobizing of stretchable elastomer surfaces is considered and the reversible behavior of the resulting surface wetting state is examined after stretching and relaxing the hydrophobized samples. The environmental dust are analyzed in terms of elemental constitutes and size, and the dust pinning on the hydrophobized surface is measured. The dust removal mechanisms, by the water droplets on the hydrophobized surface, are investigated. We demonstrated that deposition of functionalized nano-size silica units o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…When the sample was stretched 50% of its original size and then relaxed, the contact angle was found to be 132° ± 3°. The author stated that this experiment was repeated 12 times 42 . Similar to the bulk PI, the PI thin films produced in this study showed similar contact angle values even after 1000 repeated stretching and releasing cycles.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…When the sample was stretched 50% of its original size and then relaxed, the contact angle was found to be 132° ± 3°. The author stated that this experiment was repeated 12 times 42 . Similar to the bulk PI, the PI thin films produced in this study showed similar contact angle values even after 1000 repeated stretching and releasing cycles.…”
Section: Resultssupporting
confidence: 51%
“…The author stated that this experiment was repeated 12 times. 42 Similar to the bulk PI, the PI thin films produced in this study showed similar contact angle values even after 1000 repeated stretching and releasing cycles. Based on the mechanical durability results of PI thin film under repeated stretching and releasing cycle, PECVD PI thin films exhibited high durability without delamination.…”
Section: Film Structuressupporting
confidence: 57%
“…In addition, the dust particles compose of various elements and having different shapes and sizes. Some of the constituting compounds of dust do not yield stoichiometric elemental ratios while possessing ionic forces on dust surfaces, which is particularly the case for small dust particles (< 2.5 µm) 15 . Small particles tend to adhere to strong bonds on the surfaces.…”
mentioning
confidence: 99%
“…The hydrophobic wetting state of surfaces finds a wide range of applications in many fields including energy harvesting, 1 biomedical technology and medicine, 2 self-cleaning, 3 and similar.…”
Section: Introductionmentioning
confidence: 99%